2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6611098
|View full text |Cite
|
Sign up to set email alerts
|

A new ecological method for the estimation of Nutritive Sucking Efficiency in newborns: Measurement principle and experimental assessment

Abstract: The Sucking Efficiency (SEF) is one of the main parameters used to monitor and assess the sucking pattern development in infants. Since Nutritive Sucking (NS) is one of the earliest motor activity performed by infants, its objective monitoring may allow to assess neurological and motor development of newborns. This work proposes a new ecological and low-cost method for SEF monitoring, specifically designed for feeding bottles. The methodology, based on the measure of the hydrostatic pressure exerted by the liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…While the vacuum problem can be easily avoided using a commercial vented bottle, as in [ 37 ] ( Figure 4 ) or in [ 23 ], the hydrostatic pressure might also represent an important parameter to record in the case of daily home monitoring of sucking behavior, when the infant has to face this factor while bottle-feeding. Some described apparatus [ 51 , 56 ] can be adoptable for such application: they report sensing solutions based on PTs measuring the pressure at the base of the nutrient column. Moreover, these factors suggest that another important aspect in the design of a standardized feeding assessment tool, is its shape [ 65 ], as it can determine the extent of the influence of hydrostatic pressure on feeding (see Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the vacuum problem can be easily avoided using a commercial vented bottle, as in [ 37 ] ( Figure 4 ) or in [ 23 ], the hydrostatic pressure might also represent an important parameter to record in the case of daily home monitoring of sucking behavior, when the infant has to face this factor while bottle-feeding. Some described apparatus [ 51 , 56 ] can be adoptable for such application: they report sensing solutions based on PTs measuring the pressure at the base of the nutrient column. Moreover, these factors suggest that another important aspect in the design of a standardized feeding assessment tool, is its shape [ 65 ], as it can determine the extent of the influence of hydrostatic pressure on feeding (see Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, the use of air-flow sensors (thermistors or pneumotachometers) mounted on the top of the inverted nutrient reservoir, may represent a practicable sensing solution to be further investigated to increase the level of integration and develop a portable feeding tool (it also implies the resolution of the vacuum build-up problem). The solutions using PTs to measure nutrient consumption may also be easily adopted at home for a remote continuous monitoring of infant's development, but further research is suggested for their validation in field [ 23 , 56 ]. The same portability can be obtained adopting an ultrasonic flow sensor, as in [ 55 ], but it represents an expensive solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Volume estimation is based on measurement of the air pressure inside the feeding bottle. Moreover, volume estimations are independent from the tilt of the bottle with respect to gravity, so that it is not needed any orientation monitoring, or keeping the bottle at a specific angle to obtain good volume estimations, as done by [41]. Since the use of our new device does not modify how bottle feeding is commonly done (e.g.…”
Section: Experimental Validationmentioning
confidence: 99%